2015
DOI: 10.1177/0363546515599631
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hamstring Strains in 25 NCAA Sports in the 2009-2010 to 2013-2014 Academic Years

Abstract: Hamstring strain rates were higher in the preseason and in competition. Student-athletes should be acclimatized to the rigors of preseason participation. Meanwhile, further surveillance should investigate the effectiveness of prospective prevention programs in an effort to reduce the prevalence of initial and recurrent hamstring strain injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 27 publications
4
105
3
5
Order By: Relevance
“…At the same time, a larger proportion of quadriceps strains were recurrent in women compared with men, although the finding was not significant. These results differ from those of previous authors 15,31 who observed higher rates and larger proportions of recurrent hamstrings strains in men. The contrasting findings may be due to muscle-activation differences between the sexes.…”
Section: Sex Differencescontrasting
confidence: 99%
See 3 more Smart Citations
“…At the same time, a larger proportion of quadriceps strains were recurrent in women compared with men, although the finding was not significant. These results differ from those of previous authors 15,31 who observed higher rates and larger proportions of recurrent hamstrings strains in men. The contrasting findings may be due to muscle-activation differences between the sexes.…”
Section: Sex Differencescontrasting
confidence: 99%
“…Only 3.3% were classified as severe, thus providing insufficient power to detect any sex differences. These findings parallel those reported by Dalton et al 15 regarding hamstrings injuries. Because we included quadriceps strains that were NTL, it is possible that some of the reported strains represented delayed-onset muscle soreness rather than a true muscle strain.…”
Section: Participation-restriction Timesupporting
confidence: 92%
See 2 more Smart Citations
“…For example, starting status has been identified as a significant contributor to lower extremity injury among collegiate football players, 28 and injury rates are consistently higher in competition than in practice. 5 This suggests that game exposure may be an important consideration when assessing injury risk. Consequently, not accounting for sex, sport, and athletic exposure when using screening tools such as the SEBT to evaluate injury risk may result in imprecise identification of at-risk athletes.…”
mentioning
confidence: 99%